Exploring the relationship between smartphone use and ocular health in young adults: A cross-sectional study of chronic smartphone users in Salem, Tamil Nadu - Senthil Kumar Babu; Durga Murugan; Ezhil Vendhan Kalaimamani (Journal of Krishna Institute of Medical Sciences University)
Background: Recent international reports on ocular health shared that diplopia and dry eye are the prevalent ocular disorders caused by the overuse of smartphones in young adults. Studies on smartphone usage in young adults reported that smartphone use begins at the age group ranging from 12-18 years old, the minimum duration of smartphone use per day is 4-6 hrs. Aim and Objectives: To investigate the ocular impact and SmartPhone Vision Syndrome (SPVS) among chronic smartphone users. Material and Methods: The observational study was done on 100 volunteers. A structured questionnaire was used to collect the details of smartphone usage followed by the Schirmer test, visual acuity test, and Intraocular Pressure (IOP) were taken as some of the parameters in the study. Results: The continuous use of smartphones caused various problems such as headaches, eye dryness, earache, fatigue, and musculoskeletal manifestations. The Schirmer test, visual acuity, and IOP of both the right and left eye were analyzed to check out the ocular defects in chronic usage of smartphones. The ocular manifestations are noted and correlated with the duration of usage. Conclusion: It is suggested that the minimization of screen time to be educated among all age groups. It is required to spread awareness among young adults about the adverse effects of prolonged use of smartphones.